2019
DOI: 10.30704/http-www-jivs-net.568061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of milk replacer added Macleaya cordota extract calf body weight and health

Abstract: This experiment was conducted on 40 newborn Holstein female calves comprising two experimental groups, with 20 calves in each group to investigate the effects of Macleaya cordata extract (MCE), on calf body weight and health which added to milk replacer. In both group calves fed on the same terms. Differently, 10 g /head/ day dosages MCE added to the milk replacer of the trial group from day 3 to day 25. Afterward, calves continued to feed until 3 months old and weighed on the birth, 15th, 40th, 60th and 90th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Our results indicated that BS and MCE increased FPCM yields, while decreased CH 4 emissions per kilogram of FPCM. Both additives have been shown to benefit the health of cattle, BS improved digestion and increased serum IgG and IFN-γ levels [ 31 , 32 ] and MCE improved intestinal morphology and reduced the incidence of respiratory diseases based on its antibacterial and anti-inflammatory effects [ 33 , 34 ]. In agreement with our results, Choonkham et al and Souza et al [ 35 , 36 ] also reported that BS increased milk yield in dairy cows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results indicated that BS and MCE increased FPCM yields, while decreased CH 4 emissions per kilogram of FPCM. Both additives have been shown to benefit the health of cattle, BS improved digestion and increased serum IgG and IFN-γ levels [ 31 , 32 ] and MCE improved intestinal morphology and reduced the incidence of respiratory diseases based on its antibacterial and anti-inflammatory effects [ 33 , 34 ]. In agreement with our results, Choonkham et al and Souza et al [ 35 , 36 ] also reported that BS increased milk yield in dairy cows.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there were few studies on MCE in dairy cows. Previous researches have shown that MCE reduces small intestinal damage and respiratory morbidity in young animals [ 34 , 37 ]. Therefore, it could be speculated that the observed improvements in lactation performance may be due to the anti-inflammatory and immune boosting capability of MCE.…”
Section: Discussionmentioning
confidence: 99%